Risk Assessment of Human Consumption of Meat From Fenbendazole-Treated Pheasants - Carreño Gútiez, Marta; Tell, Lisa A.; Martínez-López, Beatriz (Frontiers in Veterinary Science, 2021)
Fenbendazole is a benzimidazole-class anthelmintic that is used for the control of immature and adult stages of internal parasites, such as nematodes and trematodes in domestic food-animal species. It is not approved by the USA Food and Drug Administration (FDA) for treating pheasants despite Syngamus trachea being one of the most prevalent nematodes that parasitizes pheasants. Since it is a highly effective treatment, e.g., 90% effectiveness against Syngamus trachea, and there are very few alternative therapeutic options, this anthelminthic is used in an extra-label manner in the pheasant industry but few studies have been conducted assessing risks to humans. Therefore, we conducted a risk assessment to evaluate the potential repeat dose, reproductive, teratogenic and carcinogenic human risk that may be associated with the consumption of tissues from pheasants that were previously treated with fenbendazole. We conducted a quantitative risk assessment applying both deterministic and stochastic approaches using different fenbendazole sulfone residue limits (tolerance, maximum residue limits and analytical limit of detection) established in different poultry species by the FDA, the European Medicines Agency (EMA) and other regulatory agencies in Japan, Turkey and New Zealand. Our results show that fenbendazole poses minimal risk to humans when administered to pheasants in an extra label manner and comparison of different fenbendazole sulfone residue limits can help assess how conservative the withdrawal interval should be following extra-label drug use.